AI Writing Tools to Improve Paraphrasing Skills: A Systematic Literature Review From 2021 to 2025 - Budianto, Aris; Hoesny, Mariana Ulfah; Saavedra, Analyn D. (Journal of Innovation in Educational and Cultural Research, 2026)
The emergence of AI writing tools —knowledgeable writing assistants —is very helpful for students in improving their writing skills. However, no reviews or studies discussed using AI writing software to support students' paraphrasing skills. This systematic literature review (SLR) explores the applications of AI writing tools for improving paraphrasing skills, the aspects that can be improved, and the weaknesses to anticipate when using intelligent writing assistants. This study uses a Systematic Literature Review (SLR) that reviewed primary studies from journals indexed by Scopus, Elsevier, and ProQuest between 2021 and 2025. One thousand four hundred ninety-seven raw articles were found in the search. Thirty-three articles were removed due to duplication. Verification of titles and abstracts resulted in 98 articles. The final step was full-text screening. The final screening results determined 22 articles that met the criteria. The review's findings explain the strengths and weaknesses of each AI used for paraphrasing. The findings also provide suggestions for further research in improving paraphrasing skills.